2023
DOI: 10.1002/ehf2.14634
|View full text |Cite
|
Sign up to set email alerts
|

Digital consults to optimize guideline‐directed therapy: design of a pragmatic multicenter randomized controlled trial

Jelle P. Man,
Marcel G.W. Dijkgraaf,
M. Louis Handoko
et al.

Abstract: AimsMany heart failure (HF) patients do not receive optimal guideline‐directed medical therapy (GDMT) despite clear benefit on morbidity and mortality outcomes. Digital consults (DCs) have the potential to improve efficiency on GDMT optimization to serve the growing HF population. The investigator‐initiated ADMINISTER trial was designed as a pragmatic multicenter randomized controlled open‐label trial to evaluate efficacy and safety of DC in patients on HF treatment.Methods and resultsPatients (n = 150) diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In five studies several digital and non-digital interventions were combined to a multifaceted approach [ 56 ]. Here, three studies (60%) showed positive results.…”
Section: Multifaceted Interventionsmentioning
confidence: 99%
“…In five studies several digital and non-digital interventions were combined to a multifaceted approach [ 56 ]. Here, three studies (60%) showed positive results.…”
Section: Multifaceted Interventionsmentioning
confidence: 99%